Decreased Soluble Human Leukocyte Antigen E Levels in Patients After Allogeneic Hematopoietic Stem Cell Transplantation Are Associated With Severe Acute and Extended Chronic Graft-versus-Host Disease and Inferior Overall Survival - Kordelas, Lambros; Schwich, Esther; Lindemann, Monika; Heinemann, Falko M.; Buttkereit, Ulrike; Horn, Peter A.; Beelen, Dietrich W.; Rebmann, Vera (Frontiers in Immunology, 2020)
HLA-E is a member of the non-classical HLA molecules and by interaction with activating or inhibitory receptors of NK and T cells, HLA-E can lead to immune activation or suppression context-dependently. Recently, the non-classical HLA molecules gain more attention in the setting of allogeneic hematopoietic stem cell transplantation (HSCT). Most studies so far have focused on the two most frequent genotypes (HLA-E*01:01 and HLA-E*01:03) and investigated their potential association with clinical endpoints of HSCT, like graft-versus-host disease (GvHD), relapse, and overall survival (OS). However, these studies have produced inconsistent results regarding the role of HLA-E and the clinical endpoints after HSCT. We therefore here investigate the amount of soluble HLA-E (sHLA-E) in patients following HSCT and relate this to the clinical endpoints after HSCT. In univariate analysis, we observe a significant association of reduced levels of sHLA-E with severe acute GvHD, extended chronic GvHD and with inferior OS. Using receiver operating characteristic analyses specific thresholds obtained 1, 2, or 3 month(s) after HSCT were identified being indicative for severe acute GvHD, extended chronic GvHD, or inferior OS. In sub-group analyses, this effect can be confirmed in patients not treated with ATG, but is derogated in ATG-treated patients. Notably, we could not detect any association of the course of sHLA-E levels post-HSCT with the three most frequent HLA-E genotypes (HLA-E*01:03/*01:03, HLA-E*01:01/*01:01, HLA-E*01:01/*01:03). However, with regard to 5-year-OS there was an association of HLA-E*01:03 homozygosity with inferior OS. Taking ATG-treatment, recipient and donor HLA-E genotypes into consideration among other well-known risk factors, the sHLA-E status was found as an independent predictor for the development of extended cGvHD and inferior OS following HSCT irrespective of the sHLA-E thresholds. These findings shed some light on the possible impact of reduced sHLA-E levels after HSCT on GvHD and OS. Thus, sHLA-E appears to be a novel promising candidate for the prediction of clinical HSCT outcome with regards to extended cGvHD and OS.